Indigenous youth leadership development : rediscovering youth leadership - Lickers, Michael (2016)
This Indigenous methodology (IM) and participatory action research (PAR) explored the methodologies and principles of Indigenous youth leadership (IYL). Some Indigenous researchers studying leadership and Indigenous leadership reflect on ancient tribal stories while considering the challenges of Western leadership philosophies. Although some Indigenous youth leaders are acquiring traditional leadership knowledge, practice of this knowledge is exceptionally limited. The literature review uncovers the complexity of leadership and its multidisciplinary perspectives from the point of view of Western leadership, Indigenous leadership, youth leadership, and IYL. The author presents a story of 30 First Nations youth leaders in Alberta, (Canada), with specific themes deriving from the data. A model to enhance the field of IYL is presented based on the data gathered. The stories present the youth leader's knowledge and experiences and make recommendations for IYL that include the development of an IYL centre, additional education on the knowledge of Indigenous leaders past and present, their progression towards leadership, and practical applications to realize this knowledge.